Advancements in waste water characterization through NMR spectroscopy: review. (3rd October 2014) - Alves Filho, Elenilson G.; Alexandre e Silva, Lorena M.; Ferreira, Antonio G.; Simpson, Andre J.
<x xml:space="preserve">Abstract</x> There are numerous organic pollutants that lead to several types of ecosystem damage and threaten human health. Wastewater treatment plants are responsible for the removal of natural and anthropogenic pollutants from the sewage, and because of this function, they play an important role in the protection of human health and the environment. Nuclear magnetic resonance (NMR) has proven to be a valuable analytical tool as a result of its versatility in characterizing both overall chemical composition as well as individual species in a wide range of mixtures. In addition, NMR can provide physical information (rigidity, dynamics, etc.) as well as permit in depth quantification. Hyphenation with other techniques such as liquid chromatography, solid phase extraction and mass spectrometry creates unprecedented capabilities for the identification of novel and unknown chemical species. Thus, NMR is widely used in the study of different components of wastewater, such as complex organic matter (fulvic and humic acids), sludge and wastewater. This review article summarizes the NMR spectroscopy methods applied in studies of organic pollutants from wastewater to provide an exhaustive review of the literature as well as a guide for readers interested in this topic. Copyright © 2014 John Wiley & Sons, Ltd.